Identifikasi Koi Herpesvirus dengan Uji Imunopatologi Imunohistokimia Streptavidin Biotin pada Ikan Mas Karier (IDENTIFICATION OF KOI HERPESVIRUS USING IMMUNOPATHOLOGIC IMMUNOHISTOCHEMISTRY OF STREPTAVIDIN BIOTIN IN THE COMMON CARP CARRIERS) - Wasito, Raden; Wuryastuti, Hastari; Sutrisno, Bambang (Jurnal Veteriner, 2013)
In  managing the koi herpesvirus (KHV) outbreaks as a routine national program in Indonesia, testingbased on biotechnology, such as  immunopathologic immunohistochemical approach(es) using antibodythat is safe, rapid  and accurate need to be applied. This will hopely assist the Government of Indonesianin improving and enhancing the sustainability of national animal proteins program. The present studywas aimed to develop and apply the immunopathologic immunohistochemistry of streptavidin biotin (IHCSB) for detection of KHV in the apparently normal carps. The gills from 48 common carps  (Cyprinuscarpio) that appear to be healthy were prepared for  DNA-based KHV  by IHC SB.  Common carps werecollected from fish farms which had an outbreak of KHV in 2008-2009 in Yogyakarta.  All fish werenecropsied. The gills were processed histopathologically and then stained for IHC SB with monoclonalantibody anti-KHV. We demonstrated that all of the fish gills were positive for KHV antigen. Thus, it isconcluded that method is useful and consistent, very sensitive and rapid, and is a reliable method to beapplied for field condition to detect antigen KHV in the gills of normal, healthy looking carps.   In addition,and more importantly, the fish can act as a source of KHV (carriers for KHV) and may result in the spreadof diseases among susceptible fish.
Keywords: Koi herpesvirus, immunopathologic, streptavidin, biotin, common carps, carriers, gills